New insights into the role of the oral leukoplakia microenvironment in malignant transformation - González-Arriagada, Wilfredo Alejandro; Canedo-Marroquin, Gisela; Adorno-Farías, Daniela; Fernández-Ramires, Ricardo (Frontiers in Oral Health, 2024)
Oral leukoplakia is the most frequent and potentially malignant lesion of the oral cavity. Although dysplasia grading remains the main factor for risk assessment, challenges persist in determining the exact risk of transformation, and the literature has focused on studying alternative biomarkers. The interaction between dysplastic epithelial cells and the microenvironment starts early, and the communication is mainly mediated by lymphocytes, inflammatory factors, fibroblasts, and the extracellular matrix, leading to dysplastic progression. Leukoplakia-infiltrating leukocytes (LILs) and leukoplakia-associated fibroblasts (LAFs) play crucial roles in the dysplastic microenvironment. The immune response is related to intraepithelial T lymphocyte infiltration, mechanisms of immunosuppression coordinated by regulatory T cells, M2 macrophage polarization, and increased numbers of Langerhans cells; in contrast, fibroblastic and extracellular matrix factors are associated with increased numbers of pro-tumorigenic myofibroblasts, increased expression of metalloproteinases vs. decreased expression of TIMPs, and increased expression of chemokines and other inflammatory mediators. The microenvironment offers insights into the progression of leukoplakia to carcinoma, and understanding the complexity of the oral microenvironment in potentially malignant diseases aids in determining the risk of malignant transformation and proposing new therapeutic alternatives.